2022
DOI: 10.3390/healthcare10081549
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Supply Chain Management under COVID-19 Settings: The Existing Practices in Hong Kong and the United States

Abstract: COVID-19 is recognized as an infectious disease generated by serious acute respiratory syndrome coronavirus 2. COVID-19 has rapidly spread all over the world within a short time period. Due to the coronavirus pandemic transmitting quickly worldwide, the impact on global healthcare systems and healthcare supply chain management has been profound. The COVID-19 outbreak has seriously influenced the routine and daily operations of healthcare facilities and the entire healthcare supply chain management and has brou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 45 publications
(70 reference statements)
0
6
0
Order By: Relevance
“…During the COVID-19 period, supply-based services, which include family planning and vaccinations, were more volatile than what models had predicted. The pandemic’s impact on global healthcare systems and supply chain management has been profound—the outbreak of COVID-19 created one of the most vital supply chain disruptions of the past 50 years ( 38 ). A number of major healthcare facilities (e.g., distribution centers, factories, and warehouses) were situated in COVID-19 quarantine zones in China, Italy, India, the United States, Japan, Russia, and Australia ( 39 ), which resulted in a severe scarcity of critical medical supplies.…”
Section: Discussionmentioning
confidence: 99%
“…During the COVID-19 period, supply-based services, which include family planning and vaccinations, were more volatile than what models had predicted. The pandemic’s impact on global healthcare systems and supply chain management has been profound—the outbreak of COVID-19 created one of the most vital supply chain disruptions of the past 50 years ( 38 ). A number of major healthcare facilities (e.g., distribution centers, factories, and warehouses) were situated in COVID-19 quarantine zones in China, Italy, India, the United States, Japan, Russia, and Australia ( 39 ), which resulted in a severe scarcity of critical medical supplies.…”
Section: Discussionmentioning
confidence: 99%
“…Participants also reported that the shortages of essential testing supplies and equipment amid the high testing demands elevated their stress levels. The pandemic affected the demand and supply of healthcare supplies and equipment, causing disruptions to the supply chain [39]. Participants noted that the lack of necessary supplies impeded their work, leading to delays in testing and diagnoses, compromising patient care.…”
Section: Pandemic Stressorsmentioning
confidence: 99%
“…A limitation is that there is no meaningful symbolic representation of the learned patterns, and the interpretation of the learned routine is done manually. The complexity of home healthcare under pandemic situations such as COVID-19 has been addressed in [31,32]. Routing and scheduling caregivers to visit patients' homes considering economic, environmental, and social criteria is rather difficult.…”
Section: Related Workmentioning
confidence: 99%